ANALISIS UPAYA-UPAYA PEMERINTAH DAERAH DALAM MENINGKATKAN PENDAPATAN ASLI DAERAH (PAD) DI KABUPATEN BENER MERIAH - , Rachmatan Nurul Azmi, S.T. ([Yogyakarta] : Universitas Gadjah Mada, 2013)
This study aims to examine and to analyze efforts made by the Regional Government of Bener Meriah Regency to increase Regional Original Income (PAD). The analytical devices employed in this study were growth, contribution, matrix of potential taxes and levies classification, as well as effectiveness. The data used were primary data obtained through interviews and secondary data in the form of time series (time series), they were the data on budget and the realization of Regional Original Income of Bener Meriah Regency in 2007/2008 to 2011 obtained from Local Financial and Asset Management Agency of Bener Meriah Regency. The results of this study indicated that the entertainment tax was the local tax encountering the highest average growth amounting to 67.33 percent. The local levy which had the highest average growth was the disturbance permit levy which amounted to 576.34 percent. The highest average contribution of local taxes was the street lighting tax which amounted to 5.97 percent and the highest average contribution of local levies was the market service levy which amounted to 22.44 percent. The computation results concerning Effectiveness, the Agency of Food Crops Agriculture and Horticulture was the office holding the highest level of effectiveness compared to other agencies which amounted to 84.20 percent, with the category of âquite effectiveâ. Meanwhile, seen from the whole agencies, the average effectiveness rate was only 55.29 percent, meaning that the efforts made by the Regional Government of Bener Meriah Regency in collecting PAD were considered ineffective. Local taxes of Bener Meriah Regency in the undeveloped category were the restaurant tax, the entertainment tax, the advertisement tax, the street lighting tax and the non-metal mineral tax, there were no local taxes identified as prime, potential and developing, and the remaining taxes had not been identified. Likewise, the local levies identified as the developing ones were